Beard transplantation - Carlos Eduardo Guimarães Leão (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: Beard transplantation is a surgical procedure that has been increasingly performed in the last 10 years, concurrently with the considerable technical progress of hair restoration. This is a prevalent phenomenon in plastic surgery worldwide and a great option for patients naturally beardless or with patchy beards and to hide unsightly facial scars in beard areas. METHODS: Some diseases, including alopecia areata, dermatophytosis, folliculitis, dermatitis, and emotional stress, may progress with loss of beard hair and should be clinically treated. Therefore, etiological evaluation and differential diagnosis are fundamental in the surgical indication for beard failure due to genetic problems or scars in the beard, mustache, and goatee areas. RESULTS: A good beard surgery outcome requires correct diagnosis and adequate planning for each case, refined and careful surgical technique, and perfect physician-patient relationship because facial changes are striking. CONCLUSION: This is a surgery for any individual seeking one of the most striking male esthetic attributes of all time: the beard. This surgery is an actualized aspiration for naturally beardless patients and patients with patchy beards or unsightly facial scars in beard areas and will positively affect their self-esteem, ultimately improving all aspects of their lives.